Stage_W: An applied general equilibrium model with multiple types of water. Technical documentation - Jonas Luckmann; Scott McDonald (Universität Hohenheim, Institut für Agrarpolitik und Landwirtschaftliche Marktlehre, 2014)
This document provides a description of the STAGE_W computable general equilibrium (CGE) model, which is a development of the STAGE model and allows for the depiction of diverse water resources and qualities as well as the simulation of detailed water policy scenarios. The main extensions of STAGE_W are the integration of various water resources as factors, from which specific activities produce water commodities. These commodities are used as inputs in the production process of other activities or are consumed by households and other agents as final users. Thereby, the number and specification of water factors, activities and commodities are flexible and can be adjusted to the conditions of the country analyzed. Moreover the model allows for the substitution of water commodities by water consuming activities. Besides this, the addition of two water specific tax instruments, allows for various pricing schemes, including price differentiation according to water user. All other features of the STAGE model are carried over directly to STAGE_W.
urn:nbn:de:bsz:100-opus-9843
Keywords: 330; general equilibrium model; water managment; nesting structure; water pricing; water types; Modellierung; Gleichgewichtsmodell; Wasserpreis; Produktionsstruktur; Ressourcenmanagement; Wassermanagement; Wasserverteilung